Água: a escolha da ciência - Automare, Marcio Miguel (Estudos Avançados, 2015)
Science started many centuries ago, progressing permanently. Since the 1950s it has been developing increasingly, obliging us, at the beginning of this century, to make a choice: to accept that the weather changes cause natural impacts which may be moderated by new technologies and, on the other hand, may recognize that our interventions in nature were guided by economic purpose and profit, demanding urgent changes in our habits and behaviors.